Data in support of Impact of precursor dosing on the surface passivation of AZO/AlOx stacks formed using atomic layer deposition - Wang, Y; Hobson, T; Swallow, J; McNab, S; O'Sullivan, J; Soeriyadi, A; Niu, X; Fraser, R; Dasgupta, A; Maitra, S; Altermatt, P; Weatherup, R; et al. (University of Oxford, 2025)
All data reported in publication: Impact of precursor dosing on the surface passivation of AZO/AlOx stacks formed using atomic layer deposition